2017
DOI: 10.1111/nph.14678
|View full text |Cite
|
Sign up to set email alerts
|

E3 ligase SAUL1 serves as a positive regulator of PAMP‐triggered immunity and its homeostasis is monitored by immune receptor SOC3

Abstract: In both plants and animals, intracellular nucleotide-binding leucine-rich repeat proteins (NLRs; or Nod-like receptors) serve as immune receptors to recognize pathogen-derived molecules and mount effective immune responses against microbial infections. Plant NLRs often guard the presence or activity of other host proteins, which are the direct virulence targets of pathogen effectors. These guardees are sometimes immune-promoting components such as those in a mitogen-activated protein kinase cascade. Plant E3 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 72 publications
1
79
0
Order By: Relevance
“…Phosphorylated BIK1 was recently demonstrated to be directly involved in regulating levels of the defense hormones JA and SA (Lal et al, 2018). When autoimmune effects are removed, the corresponding genes of some mutants, such as saul1 , have been shown to facilitate immune signaling (Tong et al, 2017). Similarly, when the high level of basal SA was removed by the expression of the SA dehydrogenase NahG, the sik1 knockout was compromised in flg22-induced bacterial growth inhibition and no longer exhibited enhanced resistance to virulent Pst .…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated BIK1 was recently demonstrated to be directly involved in regulating levels of the defense hormones JA and SA (Lal et al, 2018). When autoimmune effects are removed, the corresponding genes of some mutants, such as saul1 , have been shown to facilitate immune signaling (Tong et al, 2017). Similarly, when the high level of basal SA was removed by the expression of the SA dehydrogenase NahG, the sik1 knockout was compromised in flg22-induced bacterial growth inhibition and no longer exhibited enhanced resistance to virulent Pst .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that loss of SAUL1 results in autoimmunity that is dependent on SOC3 (Tong et al ., ). From the saul1‐1 suppressor screen, we did not isolate any chs1 or tn2 alleles.…”
Section: Resultsmentioning
confidence: 97%
“…As reported before, the TNL SOC3 is required for autoimmunity of both saul1‐1 and the 35S::SAUL1 transgenic line (Tong et al ., ). Based on the data mentioned above, the truncated TN protein CHS1, but not TN2, is required for the saul1‐ mediated autoimmune phenotype.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations